Lon-dependent regulation of the DNA binding protein HU in Escherichia coli. - Bonnefoy, E (1989)
HU, the major DNA binding protein of Escherichia coli, exists in solution as a heterodimer composed of two highly homologous subunits: HU1, encoded by hupB; HU2, encoded by hupA. The purification of the HU protein from hupA- or hupB- bacteria showed that the hupB mutant strains synthesize normal amounts of the HU2 subunit (which corresponds to 60% of the total HU present in wild-type cells). On the contrary, the amount of HU1 present in hupA mutant strains corresponds to only 6% of the total HU present in wild-type cells. We showed by fusions of the hupB and hupA promoters to the malPQ operon that the absence of one subunit has no major effect on the transcription rate of the gene encoding the other subunit. Analysis of the stability of the HU1 and HU2 subunits, using pulse-chase labeling experiments, showed that the HU1 subunit is degraded specifically in the absence of the HU2 subunit and, moreover, that this degradation is dependent on the presence of the Lon protease.